BsmI POLYMORPHISM OF THE VITAMIN D RECEPTOR GENE IN CHILDREN OF THE UKRAINIAN POPULATION WITH TYPE 1 DIABETES - Lukashuk, Iryna; Kvachenyuk, Dmytro; Bolshova, Olena (Collection of scientific papers «ΛΌГOΣ», 2025)
Vitamin D (vit. D) and the vitamin D receptor (VDR) gene affect human health, as they regulate the expression of genes that control calcium homeostasis, energy metabolism, and immune processes [1]. The involvement of vitamin D in the etiopathogenesis of type 1 diabetes (T1DM) cannot be ruled out.